1991
DOI: 10.1128/iai.59.12.4459-4464.1991
|View full text |Cite
|
Sign up to set email alerts
|

Protective efficacy of a 62-kilodalton antigen, HIS-62, from the cell wall and cell membrane of Histoplasma capsulatum yeast cells

Abstract: We reported previously that a detergent extract of the cell wall and cell membrane of Histoplasma capsulatum yeast cells contains antigens recognized by T cells. In T-cell immunoblot analysis, a region encompassing 62 kDa was stimulatory for an H. capsulatum-reactive T-cell line and T-cell clones derived from C57BL/6 mice. In this study, we isolated a 62-kDa band, termed HIS-62, from electrophoresed cell wall and cell membrane of H. capsulatum yeast cells and examined its antigenicity and immunogenicity. C57BL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…This study extends the reported number of protective antigens in CW/M to two. There is the 80-kDa antigen and a previously isolated 62-kDa antigen (14). The latter, however, was able to confer protection in mice against a lethal challenge that was identical to the challenge employed in this study (14).…”
Section: Discussionmentioning
confidence: 64%
“…This study extends the reported number of protective antigens in CW/M to two. There is the 80-kDa antigen and a previously isolated 62-kDa antigen (14). The latter, however, was able to confer protection in mice against a lethal challenge that was identical to the challenge employed in this study (14).…”
Section: Discussionmentioning
confidence: 64%
“…However, Hsp 60 proteins are known to indirectly modulate free Fe pools to prevent cell damage (Cabiscol et al, 2002) Production increased with limited hyphal growth (Rillig & Steinberg, 2002;Lovelock et al, 2004) Stress-protein homology Conserved/ cross-reactive among glomeromycotan fungi Hsp 60 genes are highly conserved and are used for molecular taxonomy of microorganisms (Hill et al, 2005;Zhu & Dong, 2001) Tightly mycelium or hyphal wall-bound (Driver et al, 2005) Mitochondrial target sequence, but 'moonlighting' commonly observed resulting in cell wall localization of mature protein Heat stable (extraction by autoclaving) Can survive boiling (Lewthwaite et al, 2001) GRSP, including lectin-binding and capillary electrophoresis, arrived at the conclusion that N-terminal glycosylation may be present ; this is corroborated by our findings here. Other researchers have also found that the mature Hsp 60 protein can be both glycolsylated and present in the cell wall (Gomez et al, 1991(Gomez et al, , 1995Thomas et al, 1997). It is currently not known whether glycosylation is essential to the functionality of glomalin.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant H. capsulatum HSP60 corresponding to the sequence of the unprocessed precursor of H. capsulatum HSP60 (Swiss‐Prot. P50142) from aa40–590 [18] and recombinant H. capsulatum HSP60‐derived fragment 1 (aa40–328), fragment 2 (aa131–394), fragment 3 (aa214–484) and fragment 4 (aa373–590) have been synthesized as previously described [19,20].…”
Section: Methodsmentioning
confidence: 99%